Dakwah Sosial Muhammadiyah pada Penyintas Gempa Sulawesi Barat: Studi Kasus di Dusun Ahu - Muhammad Alifuddin; Rosmini Rosmini (Al-MUNZIR, 2022)
Research on: Muhammadiyah Social Da'wah for Earthquake Survivors in Ahu Hamlet, besides aiming to find out the patterns and approaches of Muhammadiyah social da'wah to related communities, also critically analyzes the orientation and goals of the da'wah movement in question. The research data were obtained through participatory observation, in-depth interviews and document review. The data obtained were analyzed using the Miles and Huberman paradigm combined with the Von Eckarberg hermeneutic phenomenological analysis model. Referring to the description and analysis of the research data, it is concluded that MDMC's active mitigation efforts for earthquake survivors in Ahu were not only full of social activities, but also filled with preaching. The transmission of values and morals as one of the goals of da'wah, is implemented with an integral comprehensive pattern and approach. That is a pattern that combines verbal appeals (dakwah bi al-lisan) with real action on the ground (dakwah bi al-hal/amal). It is in this context that Muhammadiyah preaching for the survivors of Dusun Ahu is not just an appeal but at the same time running an institutional capacity strengthening program, with the aim that the survivors are able to face the reality of natural disasters that befall them with a positive attitude. MDMC's social da'wah movements and activities are oriented towards strengthening and dynamic social change, taking sides with weak and marginal groups and strengthening civil society for universal human progress and welfare, regardless of ethnic background, religion and organizational affiliation. Thus MDMC's active social preaching in the mitigation space is inclusive.Keywords: Da'wah, Muhammadiyah, Earthquake Survivors.